2003
DOI: 10.1261/rna.5390803
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation of transcription elongation influences the fidelity of internal exon inclusion in Saccharomyces cerevisiae

Abstract: Unknown mechanisms exist to ensure that exons are not skipped during biogenesis of mRNA. Studies have connected transcription elongation with regulated alternative exon inclusion. To determine whether the relative rates of transcription elongation and spliceosome assembly might play a general role in enforcing constitutive exon inclusion, we measured exon skipping for a natural two-intron gene in which the internal exon is constitutively included in the mRNA. Mutations in this gene that subtly reduce recogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
131
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 147 publications
(146 citation statements)
references
References 68 publications
14
131
0
Order By: Relevance
“…8,10,11,21,22 Importantly, our observation is reinforced by studies from the Struhl lab that show Set2 loss has no effect on RNA Pol II elongation rate or processivity. 70 Given that Set2/ H3K36me2 is likely functioning directly in splicing, we reasoned that Set2 and/or H3K36 methylation might be important for recruiting splicing proteins to facilitate co-transcriptional spliceosome assembly 10,11 (i.e., a recruitment model).…”
Section: Association Ofsupporting
confidence: 63%
See 4 more Smart Citations
“…8,10,11,21,22 Importantly, our observation is reinforced by studies from the Struhl lab that show Set2 loss has no effect on RNA Pol II elongation rate or processivity. 70 Given that Set2/ H3K36me2 is likely functioning directly in splicing, we reasoned that Set2 and/or H3K36 methylation might be important for recruiting splicing proteins to facilitate co-transcriptional spliceosome assembly 10,11 (i.e., a recruitment model).…”
Section: Association Ofsupporting
confidence: 63%
“…8,21,22 Further, impaired termination has also been shown to impact proper splicing in metazoan. 78 This possibility seems less likely as a recent report revealed that deletion of SET2 had no impact on RNA Pol II elongation or processivity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations